2020
DOI: 10.4274/tjh.galenos.2020.2019.0262
|View full text |Cite
|
Sign up to set email alerts
|

Factor 8 Gene Mutation Spectrum of 270 Patients with Haemophilia A: Identification of 36 Novel Mutations

Abstract: Amaç: Hemofili A (HA), faktör 8 (F8) genindeki hemizigot mutasyonların neden olduğu X'e bağlı kalıtsal kanama bozukluğudur. Bu çalışmanın amacı, Türkiye'den büyük bir HA kohortunda F8 geninin mutasyon spektrumunu belirlemek ve fenotip-genotip korelasyonu oluşturmaktır. Gereç ve Yöntemler: Mart 2017-Mart 2018 tarihleri arasında Ege Üniversitesi Pediatrik Genetik Moleküler Laboratuvarı'nda moleküler olarak analiz edilen tüm HA hastaları (270 hasta) çalışmaya dahil edildi. "İntron 22 inversiyonu" (Inv22), "intron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 27 publications
(37 reference statements)
1
13
2
Order By: Relevance
“…In a study in Turkey, the examination of 270 patients with HA revealed a significant correlation between high‐risk genotypes and inhibitor formation. In our study, however, no significant difference was found between the mutation risk group and inhibitor development 33 . The lack of correlation in the present study can be attributed to the high prevalence of inhibitors in patients with splice errors, as documented in one previous study.…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…In a study in Turkey, the examination of 270 patients with HA revealed a significant correlation between high‐risk genotypes and inhibitor formation. In our study, however, no significant difference was found between the mutation risk group and inhibitor development 33 . The lack of correlation in the present study can be attributed to the high prevalence of inhibitors in patients with splice errors, as documented in one previous study.…”
Section: Discussioncontrasting
confidence: 88%
“…In our study, however, no significant difference was found between the mutation risk group and inhibitor development. 33 The lack of correlation in the present study can be attributed to the high prevalence of inhibitors in patients with splice errors, as documented in one previous study. Furthermore, missense variations are associated with an overall lower risk of inhibitor development; however, different missense Note: P-value, probability value; significance level was set at P < .05.…”
Section: Discussioncontrasting
confidence: 44%
“… 12 In detail, the deleterious F8 mutations, such as large deletions or insertions and nonsense mutations destructively affect the gene structure, transcription, and translation, resulting in almost complete absence of FVIII in blood circulation, which were mostly associated with the development of inhibitors. 12 , 13 Garagiola et al 4 proposed that the F8 mutation types could be divided into high‐, medium‐, and low‐risk groups, with the above‐mentioned deleterious F8 mutations boding the highest risk of inhibitor development. The current study with the large patient cohort investigated confirmed that the high‐risk F8 gene mutation types had the highest incidence of high‐titer inhibitor and also tended to have higher peak inhibitor titer.…”
Section: Discussionmentioning
confidence: 99%
“…The immune response to FVIII replacement treatment may be due to a lack of central tolerance to FVIII protein 12 . In detail, the deleterious F8 mutations, such as large deletions or insertions and nonsense mutations destructively affect the gene structure, transcription, and translation, resulting in almost complete absence of FVIII in blood circulation, which were mostly associated with the development of inhibitors 12,13 . Garagiola et al 4 proposed that the F8 mutation types could be divided into high‐, medium‐, and low‐risk groups, with the above‐mentioned deleterious F8 mutations boding the highest risk of inhibitor development.…”
Section: Discussionmentioning
confidence: 99%
“…It should be done routinely for severe to moderate hemophilia but is less frequently needed for mild hemophilia. For hemophilia B, full gene sequencing is usually done for F9, whereas inversions of intron 22 (40% frequency) and intron 1 (1%) is initially studied for severe hemophilia A (14). Since hemophilia A families with mild to moderate disease are more likely (approximately 90%) to have a point mutation, whole gene sequencing is recommended in families with mild to moderate disease if genetic testing is indicated (15).…”
Section: Diagnosis In Hemophiliamentioning
confidence: 99%